PENGELOLAAN FASILITAS DI OBJEK WISATA MASJID AGUNG MADANI ISLAMIC CENTER ROKAN HULU - Roza Silvia; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Based on field observation there are some problems concerning the management of Mosque Agung Madani Islamic Center Rokan Hulu regency which is management of Mosque Agung Madani Islamic Rokan Hulu tourism object is not good. It deservase the attention of the government to be more active in the management of Mosque Agung Madani Islamic Center Rokan Hulu. The purpose of this research is to know the management Mosque Agung Madani Islamic Center Rokan Hulu tourism objek in and factors influencing the management of Fasilities Mosque Agung Madani Islamic Center Rokan Hulu.The concep of theory used is the management of facilities theory by Spillane which starts from the Main Facility,Facility and Supporting Facilities. This research uses qualitative descriptive research method, The type of data used is primary data and scondary data. In the data collecting researchrs using observation techniques, interviews, and literature study. Interviews were conducted with informants namely the Head of the Management Agency of the Great Mosque of Madani Isalamic Center, the Secretary, visiting tour, and the staff. The results of this study resulted in the conclusion the the management of Facilities Mosgue Masjid Agung Madani Islamic Center Rokan Hulu has not been maximized. Then there is still a lack of factors that hinder the Management of Tourism Objects at Rokan Hulu Islamic Center Madani Islamic Center, namely human resources, budget, facilities and infrastructure.                                                                                                Keywords :Management of Facilities, Tourist Attraction